Functioning and post-school transition outcomes for young people with Down syndrome - Foley, K.; Jacoby, P.; Girdler, Sonya; Bourke, J.; Pikora, T.; Lennox, N.; Einfeld, S.; Llewellyn, G.; Parmenter, T.; Leonard, H. (Blackwell Scientific Publications, 2013)
Aim: To investigate the relationship between functioning and post-school day occupation for young adults with Down syndrome. Methods: Families of young people with Down syndrome (n = 269) aged 15–30 years in 2009 were recruited from the population-based Down syndrome ‘Needs Opinion Wishes’ database in Western Australia. Questionnaires were mailed to participating families and involved two parts, young person characteristics and family functioning; 203 were returned (75%). Of those families who returned questionnaires, 164 (80.8%) of their young adults had left school. Participation in post-school day occupations was the main outcome and included; open employment, training, sheltered employment or alternatives to employment (ATE). Results: Young adults were reported as participating in open employment (n = 42), training (n = 17), sheltered employment (n = 64) or ATE (n = 41) post-school. Those who reported better functioning in self-care, community and communication skills were more likely to be in open employment and/or attending Technical and Further Education compared with those attending sheltered employment and/or ATE after adjusting for age, gender and rural/metropolitan regions. Current health as measured by visits to a general practitioner (GP) and hospitalizations revealed a weak relationship with post-school day occupations, with increasing likelihood of participating in open employment or training with increasing hospitalizations and GP visits. Conclusions: Our analysis shows that functioning in activities of daily living was related to post-school day occupation. Current health status and behaviour were found to have a weak relationship with post-school day occupation adjusting for functioning in the final model.